2020
DOI: 10.3847/1538-3881/ab62a3
|View full text |Cite
|
Sign up to set email alerts
|

Yarkovsky Drift Detections for 247 Near-Earth Asteroids

Abstract: The Yarkovsky effect is a thermal process acting upon the orbits of small celestial bodies, which can cause these orbits to slowly expand or contract with time. The effect is subtle ( au My−1 for a 1 km diameter object) and is thus generally difficult to measure. We analyzed both optical and radar astrometry for 600 Near-Earth Asteroids (NEAs) for the purpose of detecting and quantifying the Yarkovsky effect. We present 247 NEAs with measured dri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 35 publications
6
62
1
Order By: Relevance
“…As of this writing, there are published A 2 values for 244 NEAs on the JPL Small-Body Database. Yarkovsky drift rate detections for an additional 149 NEAs have also been reported in Greenberg et al (2020). The largest reported diameters among these asteroids belong to the 6.25 km (3200) Phaethon and 5.4 km (4179) Toutatis.…”
Section: Yarkovsky Follow-upmentioning
confidence: 74%
“…As of this writing, there are published A 2 values for 244 NEAs on the JPL Small-Body Database. Yarkovsky drift rate detections for an additional 149 NEAs have also been reported in Greenberg et al (2020). The largest reported diameters among these asteroids belong to the 6.25 km (3200) Phaethon and 5.4 km (4179) Toutatis.…”
Section: Yarkovsky Follow-upmentioning
confidence: 74%
“…Using both models simultaneously ( 1 , 2 , 3 , and a Δv), we can determine the upper limit on these parameters to be 10 −11 , 10 −13 , and 10 −11 au/ 2 , and 10 −6 km/s respectively. These upper limits are 100 to 10,000 time smaller than usual values found for comets (Królikowska 2020) but 10 to 100 time higher than the typical values for the Yarkovsky effect for Near Earth object (Greenberg et al 2020). Excluding data prior to 2016, 2012, 2008, 2004, and 2000 also resulted in a non-detection of non-gravitational accelerations.…”
Section: Non-gravitational Accelerationmentioning
confidence: 56%
“…A small drift in semi major-axis can also be measurable thanks to accurate astrometry deriving, for example from radar measurements, but they remain rare. Since this study, various papers have identified NEAs with a measurable drift in semi-major axis using astrometry (Nugent et al 2012;Farnocchia et al 2013;Desmars 2015;Del Vigna et al 2018;Greenberg et al 2020). Thanks to better recent as-trometry, such a drift is now measurable with reliability for more than 200 objects.…”
Section: Nongravitational Accelerationmentioning
confidence: 99%